Konflik Norma Peraturan Perundang-Undangan dalam Tindak Pidana Kekerasan Seksual Berbasis Elektronik - Destri Aulia; Muhammad Ikhwan; Lukman Firnando Putra (CV Rewang Rencang, 2025)
This study aims to determine the conflict of norms and resolution of norm conflicts regarding electronic based sexual violence. Legal research with normative research, descriptive analysis, with a legislative approach. Data collection techniques from literature studies. The results of the study are the conflict of norms of Article 27 paragraph (1) of Law Number 1 of 2024 concerning Electronic Information and Transactions with Article 14 paragraph (1) of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, there are similarities in the rules regarding the distribution of photo or videos because they create doubts for law enforcement in deciding charges and Case Number 301/Pid.Sus/2024/PN Nnk, it is seen that the resolution of norm conflicts uses the principle of Lex Specialist Systematische.